Dashboard Kepegawaian Sekretariat Daerah Kabupaten Ogan Komering Ilir - Hasim Asngari (Jurnal Ilmu Komputer dan Sistem Informasi |JIKSI|, 2022)
A dashboard is an information display that can present data in a visual form. Few and Eckerson (2006) defined the information on the Dashboard system not only by presenting data but also by combining it with visual displays, so that the information presented is easier to capture the intent and results. However, this system has not been used optimally by agencies that require data processing with a graphical visual display. This is what lies behind the design of this system as an information system that can be used by the Regional Secretariat of Ogan Komering Ilir Regency to be able to check and monitor staffing data within the Ogan Komering Ilir Regency Regional Secretariat. The system development method used is FAST (Framework for the Application of System Thinking). The results show that this system works well and can be used as an integrated information system that can visually and comprehensively present data to executives as decision makers and make it easier for employees to input and process existing data. In addition, the design of this dashboard system is considered more ergonomic, responsive, interactive, and accurate in practice.